The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/preaccept-8144459901289378
|View full text |Cite
|
Sign up to set email alerts
|

BI-2 destabilizes HIV-1 cores during infection and Prevents Binding of CPSF6 to the HIV-1 Capsid

Abstract: Background: The recently discovered small-molecule BI-2 potently blocks HIV-1 infection. BI-2 binds to the N-terminal domain of HIV-1 capsid. BI-2 utilizes the same capsid pocket used by the small molecule PF74. Although both drugs bind to the same pocket, it has been proposed that BI-2 uses a different mechanism to block HIV-1 infection when compared to PF74. Findings: This work demonstrates that BI-2 destabilizes the HIV-1 core during infection, and prevents the binding of the cellular factor CPSF6 to the HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Following viral entry, the capsid undergoes controlled disassembly (uncoating), which seems coordinated with reverse transcription (7,9). Antivirals targeting CA (12)(13)(14)(15)(16)(17) include PF-3450074 (PF74), which has a bimodal mechanism of action (18)(19)(20)(21). At lower concentrations (nanomolar to ~2 mM), it competes with binding of host factors CPSF6 and NUP153, affecting nuclear entry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following viral entry, the capsid undergoes controlled disassembly (uncoating), which seems coordinated with reverse transcription (7,9). Antivirals targeting CA (12)(13)(14)(15)(16)(17) include PF-3450074 (PF74), which has a bimodal mechanism of action (18)(19)(20)(21). At lower concentrations (nanomolar to ~2 mM), it competes with binding of host factors CPSF6 and NUP153, affecting nuclear entry.…”
mentioning
confidence: 99%
“…At lower concentrations (nanomolar to ~2 mM), it competes with binding of host factors CPSF6 and NUP153, affecting nuclear entry. At higher concentrations, PF74 blocks uncoating and reverse transcription (18)(19)(20)(21)(22)(23). Crystal structures of PF74 with CA NTD (CA NTD -PF74 ) (14) or cross-linked CA hexamers (CA XL-PF74 ) (18,19) have shown that PF74 binds at the same site as CPSF6 and NUP153.…”
mentioning
confidence: 99%
“…As shown in Figure a, 3G11 did not change the stability of the HIV‐1 core during infection. As controls, we used the small‐molecule HIV‐1 inhibitors PF74 and Bi‐2, which are known to destabilize the core during infection . As shown in Figure a, 3G11 did not change the stability of the HIV‐1 core during infection when compared to the use of PF74 or BI‐2.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, several proteins, drugs, and peptides that target capsid have been discovered: rhesus TRIM5α, owl monkey TRIMCyp, PF74, BI‐2, CAP‐1, Ebselen, the peptide CAI, and others. From studies using these proteins, drugs, and peptides, we have learned much about the early steps of HIV‐1 replication: (i) reverse transcription occurs before or during uncoating, (ii) the decreased stability of the HIV‐1 core, acceleration of uncoating, caused by rhesus TRIM5α, owl monkey TRIMCyp, the small‐molecule PF‐74, or the small‐molecule Bi‐2, prevents HIV‐1 infection, (iii) the increased stability of the HIV‐1 core, inhibition of uncoating, caused by the cytoplasmic expression of human CPSF6 or human MxB, similarly prevents HIV‐1 infection, and (iv) inhibition of reverse transcription increases stability of the HIV‐1 core . Altogether this evidence indicates that the HIV‐1 uncoating process is fundamentally linked to reverse transcription.…”
Section: Introductionmentioning
confidence: 99%